2020
DOI: 10.1212/wnl.0000000000009951
|View full text |Cite
|
Sign up to set email alerts
|

Association of prestroke metformin use, stroke severity, and thrombolysis outcome

Abstract: Objective:To evaluate whether pretreatment with metformin (MET) is associated with less stroke severity and better outcome after intravenous thrombolysis (IVT), we analyzed a cohort of 1919 stroke patients with type-2 diabetes in a multicenter exploratory analysis.Methods:Data from patients with diabetes affected by ischemic stroke treated with IVT were collected within the European Thrombolysis in Ischemic Stroke Patients (TRISP) collaboration. We applied propensity score matching (PSM) to obtain balanced bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 26 publications
(24 reference statements)
4
24
1
Order By: Relevance
“…It is important to mention that recent clinical studies revealed that pre-treatment with metformin resulted in less severe strokes, beneficial thrombolysis outcome and reduced neurological deficits in diabetic patients [48,49]. Thus, these results suggest that metformin has a neuroprotective effect, although there is a lack of post-ischemic treatment studies in non-diabetic patients.…”
Section: Discussionmentioning
confidence: 91%
“…It is important to mention that recent clinical studies revealed that pre-treatment with metformin resulted in less severe strokes, beneficial thrombolysis outcome and reduced neurological deficits in diabetic patients [48,49]. Thus, these results suggest that metformin has a neuroprotective effect, although there is a lack of post-ischemic treatment studies in non-diabetic patients.…”
Section: Discussionmentioning
confidence: 91%
“…The Insulin Resistance Intervention after Stroke (IRIS) trial which involved 3876 patients, demonstrated that pioglitazone, an insulin-sensitizer, reduced the risk of recurrent stroke and myocardial infarction in patients without diabetes who had recent ischemic stroke or TIA 11 . Others observed associations between prior metformin use and better neurological outcomes in patients with AIS and those who received thrombolytic therapy 60 . A meta-analysis on glucagon-like peptide-1 (GLP-1) receptor agonists like liraglutide, which work by glucose-dependent insulin release, have shown benefits for primary stroke prevention 61 .…”
Section: Discussionmentioning
confidence: 99%
“…The recent literature has hinted that metformin plays a beneficial role in improving the poor prognoses of patients with brain injury. A multicenter retrospective analysis indicated that stroke patients with diabetes who were treated with metformin showed less-severe stroke on admission and better functional outcomes at 3 months than stroke patients with diabetes who were not treated with metformin ( Westphal et al, 2020 ). Therefore, whether metformin can improve the long-term outcomes of SAH and whether it exerts beneficial clinical effects on SAH patients must also be considered in future studies.…”
Section: Discussionmentioning
confidence: 99%